The role and influence of the Irish Missions of the Society of Jesus on the implementation of a counter-reformation among the old English in Ireland, 1542-1633 - Jackson, Brian Stewart (Trinity College (Dublin, Ireland). Department of History, 2007)
This thesis seeics to present a study of the activity of the Society of Jesus and its engagement with Ireland. The study will look at the period from 1542 when Jesuits first came to Ireland, until 1633, when Wentworth arrived as viceroy. The study seeks to make a contribution to our understanding of the nature of the Counter-Reformation in an Irish context.
Keywords: Modern History, Ph.D.; Ph.D. Trinity College Dublin